Kajian Kesiapan Penerapan Proyek Penguatan Profil Pelajar Pancasila (P5) Dalam Menyongsong Penerapan Kurikulum Merdeka Berdasarkan Persepsi Guru Sebagai Tenaga Pendidik di SMKS Karsa Mulya Palangka Raya - Tarita Aprilani Sitinjak; Ni Putu Diah Agustin Permanasuri; Whendy Trissan (Jurnal Ilmiah Kanderang Tingang, 2023)
The specific aim of this research is to examine how the readiness of Karsa Mulya Vocational School is seen by teachers as educators, in implementing P5 in the independent curriculum. This research is basic research, which is oriented towards explanations to anticipate a symptom/phenomenon that arises with the project to strengthen the profile of Pancasila students (P5) to support the implementation of the independent curriculum. The theme of this research includes improving Human Resources (HR). The total time for conducting the research was one year, starting from observation, data collection, data analysis and reporting. Secondary data collection was carried out by observation and interviews, while primary data was collected using a questionnaire as a research instrument to find out the opinions of teachers as teaching staff regarding readiness. and implementing a project to strengthen the profile of Pancasila students (P5). The results of research on aspects of teacher readiness in preparing teaching module instruments and project modules from P5 were 3.61. Analysis of the readiness of aspects of school infrastructure and school ecosystem according to teaching staff is shown with a value of 4.2, which means they are ready to support the implementation of P5. This refers to the conversion of the Benchmark Reference Approach (PAP), the value of X (average of each aspect) is 4.2, so X is on a scale of 4 because 3.4<X 4.2.